Why Is American Fiction in Its Current Dismal State? - Shivani, Anis (Pleiades, 2007)
This essay is about contemporary American fiction. The author discussed the reasons why American fiction is in its current dismal state. Additionally, he remarked that the scope of such fiction is restricted too much to the trivial domestic sphere, promoting grief, paralysis, and post-politics society. He further commented on writers of fiction as well as their way of writing.